2002
DOI: 10.1097/01823246-200213020-00013
|View full text |Cite
|
Sign up to set email alerts
|

Fitness, Acute Exercise, and Anabolic and Catabolic Mediators in Cystic Fibrosis.

Abstract: Exercise can stimulate catabolic inflammatory cytokines even in healthy children. For patients with cystic fibrosis (CF), this may be problematic because CF is characterized by increased inflammation and suppressed growth. We examined fitness and the response to brief exercise of interleukin-6 (IL-6), tumor necrosis factor-␣ (TNF-␣), insulinlike growth factor-I (IGF-I), and IGF binding protein-1 (IGFBP-1) in 14 subjects with CF (10.5 Ϯ 0.8 yr of age), 9 of whom were treated with ibuprofen, and 14 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
2
24
0
4
Order By: Relevance
“…However, more recent studies have also identified immunomodulatory effects of regular physical exercise, including reduced susceptibility to viral illness, improved redox balance in the lung, and attenuated inflammatory responses to bacterial products such as LPS . Other studies have demonstrated the converse: brief intense or prolonged vigorous exercise may temporarily increase inflammation in the lung and susceptibility to infection . Therefore, the effects of exercise on pulmonary inflammation may be mixed, and large, well‐designed clinical trials testing this approach to anti‐inflammatory therapy have not been conducted.…”
Section: Promising Approaches Toward Effective and Safe Anti‐inflammamentioning
confidence: 99%
“…However, more recent studies have also identified immunomodulatory effects of regular physical exercise, including reduced susceptibility to viral illness, improved redox balance in the lung, and attenuated inflammatory responses to bacterial products such as LPS . Other studies have demonstrated the converse: brief intense or prolonged vigorous exercise may temporarily increase inflammation in the lung and susceptibility to infection . Therefore, the effects of exercise on pulmonary inflammation may be mixed, and large, well‐designed clinical trials testing this approach to anti‐inflammatory therapy have not been conducted.…”
Section: Promising Approaches Toward Effective and Safe Anti‐inflammamentioning
confidence: 99%
“…A similar lack of research surrounds the immune effects of exercise in people with chronic inflammatory diseases and conditions. In cystic fibrosis, a disease characterized by chronic infection and persistently elevated levels of inflammatory cytokines like IL-6, exercise leads to larger acute increases in IL-6 than observed in controls in both children and adults (56,143). In systemic lupus erythematosis, a systemic autoimmune disease (134), brief exercise leads to abnormal cortisol, prolactin, and CD4ϩ/CD8ϩ T-cell responses (110).…”
Section: Lessons Learned From Dysregulated Immune Responses To Exercisementioning
confidence: 99%
“…The work rate was individualized for each child and was calculated to be equivalent to the work rate corresponding to 50% between the ventilatory/lactate threshold (as determined noninvasively from the ramp-type test) and the peak V O2. We have used this protocol in the past to ensure that the exercise input was standardized to physiological indicators of each subject's exercise capacity (42). The total duration of the exercise session is 30 min (20-min cycling interspersed by 10-min resting).…”
Section: Exercise Protocolmentioning
confidence: 99%